RANCANG BANGUN ALAT MONITORING OUTPUT MODUL PLTB (PEMBANGKIT LISTRIK TENAGA BAYU (ANGIN), BERBASIS DATA LOGGER - Ajeng Ayu Maike; Rizana Fauzi; Mery Subito; Tan Suryani Sollu; Alamsyah Alamsyah (Foristek, 2022)
The PLTB module output monitoring system (wind (wind)) is based on a data logger, which in this study was carried out by designing a tool using an INA219 sensor to measure current and voltage, and using Arduino Uno as a data controller and liaison as well as sending the measurement data. sensor to a Laptop whose readings use the PLXdaq application. Based on the research that has been done, this monitoring system shows that it is an efficient and portable monitoring system and PLTB data can be accessed easily via a laptop and can be read directly using the LCD (liquid crystal display). Where the measurement results are in the form of quantities that are in accordance with the measured units such as A (amperes ) for current and V ( voltage ) for voltage, where the results will be displayed through the PLXdaq application in real time. The results of sending current and voltage data on the PLXdaq application have an error that does not exceed 1%.